Study Protocol: It is time to dig deeper: A cross-country implementation mapping study of the iFightDepression® (online self-management) tool - Thomas Rotter; Milica Petrovic; Mikołaj Zarzycki; Caroline Allenhof; Katharina Schnitzspahn; Piotr Toczyski; Azucena Justicia; Saiko Allende Leal; James Chan; Johannes Leimhofer; Katharina Scholze; Stefan Hackel; et al. (PLoS ONE, 2026)
Background The iFightDepression® (iFD) tool is an internet-based self-management program for individuals with milder forms of depression, used alongside support from trained user guides (e.g., family physicians). Despite strong evidence supporting guided internet-based cognitive behavioural therapy (iCBT), adherence to the iFD tool and its uptake across implementing countries remain variable. Methods This implementation mapping study will be conducted in Germany, Poland, and Spain. Guided by the Consolidated Framework for Implementation Research (CFIR), we aim to identify barriers, facilitators, and country-specific implementation strategies. In Phase 1, we will invite 15 trained iFD user guides to complete an online qualitative survey to explore user experiences and perceived influences on patient uptake and adherence. In Phase 2, three country-specific focus groups will be conducted with trained user guides (one in each country). Survey data will be analyzed using Interpretative Phenomenological Analysis (IPA) and focus group data will be analyzed using template analysis. Discussion Findings will be used to develop an iFD implementation manual and country-specific implementation blueprints. These outputs are intended to support consistent and sustainable adoption of this internet-based intervention across participating countries and to improve patient uptake and adherence. Study registration The study, including the analysis plan, has been preregistered via the Open Science Framework (internet archive link: https://archive.org/details/osf-registrations-wmbhy-v1 ) following ethical approval.